PENERAPAN METODE DISKUSI DALAM MENINGKATKAN KEMAMPUAN GURU MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR DI SD NEGERI 007 KOTA LAMA KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Suhartatik ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
From preliminary observations made in SD Negeri 007 Kota Lama, teachers in these schoolstake advantage of the school environment as a learning resource only two to three times inone semester. Teachers are more frequently present lessons in the classroom despite thepresented materials related to the school environment. From the interviews conductedprospective researchers, most of the teachers admitted reluctantly invites students to learnoutside the classroom, for reasons difficult to supervise. In addition there are teachers whosaid that they could not and did not know in the use of the school environment as a learningresource. Based on these issues, school action research was conducted with the aim ofimproving the ability of teachers to utilize the school environment as a learning resource andto identify the weaknesses and strengths as discussions on the improvement of teacher'sability to utilize the school environment as a learning resource in SD Negeri 007 Kota Lama.This study was designed in the form of Action Research School planned conducted in twocycles. The subjects of this study were teachers at SD Negeri 007 Kota Lama, amounting to18 people classroom teachers. Pursuant to the research note that there is an increase in theability of teachers to utilize the school environment as a learning resource approachDiscussion on SD Negeri 007 Kota Lama. By leveraging the advantages of discussion in theworking group of teachers (KKG), will be able to solve the problems faced by teachersespecially those associated with the use of the school environment as a learning resource inthe teaching and learning process in SD Negeri 007 Kota Lama. Generally seen an increasein the ability of teachers in using schools as a learning resource. The increase was mainly onthe ability categorized good, based on the indicators of research is also known that the abilityof teachers in the second cycle reaches indicators that have been established, ie the ability ofteachers are categorized either achieved amounted to 81.8%, meaning that this figure hasexceeded the success rate has been set, ie 70%.